Through the looking glass: making the design and output of economic models useful for setting medical policy. (January 2014) - Ollendorf, Daniel A; Pearson, Steven D
Economic modeling has rarely been considered to be an essential component of healthcare policy-making in the USA, due to a lack of transparency in model design and assumptions, as well as political interests that equate examination of cost with unfair rationing. The Institute for Clinical and Economic Review has been involved in several efforts to bring economic modeling into public discussion of the comparative value of healthcare interventions, efforts that have evolved over time to suit the needs of multiple public forums. In this article, we review these initiatives and present a template that attempts to 'unpack' model output and present the major drivers of outcomes and cost. We conclude with a series of recommendations for effective presentation of economic models to US policy-makers.